'n Ondersoek na die taal- en literêr-historiese arbeid van J. Du P. Scholtz - Nel, Marieta (Afrikaans and Netherlandic Studies, 2019)
The problem postulate which has led to this investigation is the discrepancy between on the one hand the perception of Scholtz's research as the norm to which Afrikaans linguistics is gauged and on the other hand the self-evident ignorance of his work by the average Afrikaans/Nederlands graduate. The subject is: An investigation into the linguistic and literary historic work of J. du P. Scholtz. The intention is to attempt to indicate the entire spectrum of Scholtz's research in these spheres. In order to give a complete picture of his contribution to Afrikaans one should describe the linguistic and literary historic contributions. His work as a cultural and art historian will be mentioned only briefly. Chapter 1 contains the results and analysis of an empirical investigation which was directed into an evaluation of Scholtz's work. In doing so an attempt is made to indicate that the above mentioned ignorance is not merely a personal and imagined scenario: Subsequently chapter 2 points out certain hitherto unknown biographical details and chapter 3 gives a comprehensive chronological outline of Scholtz's publications in an attempt to support the view of him as the norm according to which Afrikaans linguistics is gauged. This is followed by a comprehensive spectrum of his contributions with the focus primarily on his linguistic contributions in chapter 4. Raidt viewed his work from a chronological perspective in_order to trace his development but it is also. important, however, to illustrate the various spheres in which he operated. The entire range, viz diachronic and synchronic linguistics, lexicology, lexicography, linguistic textual analyses, linguistic criticism, socio-historic linguistics and correspondence with linguists is illustrated.